Colour stability of acrylic resin denture teeth after immersion in different beverages - Arana-Correa, Beatriz Elena; Sepúlveda-Navarro, Wilmer; Florez, F.L.E.; Urban, Vanessa Migliorini; Jorge, Janaina Habib [UNESP]; Campanha, Nara Hellen (My University, 2014)
The colour stability of acrylic resin denture teeth in beverages was investigated. A spectrophotometer measured the colour (CIE-L*a*b* system) of all specimens after storage in distilled water for 24 h at 37°C (T0). Specimens were then immersed in various beverages. After 15 days (T1) and 30 days (T2), for each material, the mean ∆E values were calculated and compared by two-way ANOVA and Tukey intervals (α=0.05). In the ∆T0T1 period, specimens stored in red wine were significantly discoloured, compared to distilled water (P=0.003). There was no difference between immersion solutions in ∆ET0T2 (P=0.772) and in ∆ET1T2 (P=0.058), and no difference between materials in all immersion periods.
Keywords: Acrylic resin denture teeth; Acrylic resin materials; Beverages; Colour; Colour measurement